Simultaneous observations of a Mesospheric Inversion Layer and turbulence during the ECOMA-2010 rocket campaign - Szewczyk, A.; Strelnikov, B.; Rapp, Markus; Strelnikova, I.; Baumgarten, G.; Kaifler, N.; Dunker, T.; Hoppe, U.-P. (Annales Geophysicae, 2013)
From 19 November to 19 December 2010 the fourth and final ECOMA rocket campaign was conducted at Andøya Rocket Range (69° N, 16° E) in northern Norway. We present and discuss measurement results obtained during the last rocket launch labelled ECOMA09 when simultaneous and true common volume in situ measurements of temperature and turbulence supported by ground-based lidar observations reveal two Mesospheric Inversion Layers (MIL) at heights between 71 and 73 km and between 86 and 89 km. Strong turbulence was measured in the region of the upper inversion layer, with the turbulent energy dissipation rates maximising at 2 W kg−1. This upper MIL was observed by the ALOMAR Weber Na lidar over the period of several hours. The spatial extension of this MIL as observed by the MLS instrument onboard AURA satellite was found to be more than two thousand kilometres. Our analysis suggests that both observed MILs could possibly have been produced by neutral air turbulence.